1981
DOI: 10.1042/bj2000257
|View full text |Cite
|
Sign up to set email alerts
|

Human somatotropin binding to rabbit kidney microsomal fraction

Abstract: Specific binding of 125I-labelled human somatotropin was demonstrated in microsomal membranes (microsomes) from rat and rabbit kidneys. Female rabbit kidney microsomes showed the highest binding activity and were used for further study. The association of 125I-labelled human somatotropin was time- and temperature-dependent and the binding reaction was reversible. Scatchard analysis of saturation data indicated a dissociation equilibrium constant, KD, of 56 pM and a binding capacity of 37 fmol per mg of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For this study 7 ng [ 125 I]iodo-hGH (~2 x 10 6 cpm) was incubated with 5 x 10 7 human fetal skin fibroblasts in a 75 cm 2 tissue culture flask for 2 h at 30 C. The monolayer was then washed twice with hormone-free medium and extracted as described by Roguin et al (16). Aliquots of the original [ 125 I]iodo-hGH, the unbound [ 125 I]iodo-hGH, and monolayer bound [ 125 I]iodo-hGH were precipitated by the addition of 10% TCA, centrifuged, and decanted.…”
Section: Degradation Studiesmentioning
confidence: 99%
“…For this study 7 ng [ 125 I]iodo-hGH (~2 x 10 6 cpm) was incubated with 5 x 10 7 human fetal skin fibroblasts in a 75 cm 2 tissue culture flask for 2 h at 30 C. The monolayer was then washed twice with hormone-free medium and extracted as described by Roguin et al (16). Aliquots of the original [ 125 I]iodo-hGH, the unbound [ 125 I]iodo-hGH, and monolayer bound [ 125 I]iodo-hGH were precipitated by the addition of 10% TCA, centrifuged, and decanted.…”
Section: Degradation Studiesmentioning
confidence: 99%
“…As a result, only the lactogenic sites and their characteristics may be detected by using 125I-labelled human somatotropin as ligand. (b) The presence of binding sites specific for lactogenic hormones was described in rat (Marshall et al, 1975;Mountjoy et al, 1980) and rabbit kidney (Roguin et al, 1981(Roguin et al, , 1982. Mountjoy et al (1980) reported that the specific binding activity is about 5 times higher in male than in female rat kidney.…”
Section: Discussionmentioning
confidence: 99%